Posisi Tawar Timor Leste untuk Memperoleh Status Keanggotaan Penuh di ASEAN - Rohani, Dian Ayu; Sunarko, Bagus Sigit; Soelistijono, Pra Adi (e-Sospol, 2016)
Abstract After more than a decade as an observer, Timor Leste’s application to become the eleventh member of the ASEAN has officially submitted on 4 March 2011. Indeed, despite being the youngest country in ASEAN, Timor Leste has already made substantial contributions to the region of South East Asia through its involvement in several ASEAN events included the ASEAN Regional Forum (ARF) in 2005. The problem is that there are some doubts of its ability to fulfil all the membership obligations at this time. While Indonesia is actively sponsoring Timor Leste’s application for membership in ASEAN and strongly believes that this country is ready to becoming part of the ASEAN Community, some suppose that Timor Leste is not yet ready. The purpose of this study is to evaluate the position of Timor Leste in its attempts to join the ASEAN. The study employs qualitative analysis and utilizes some models of diplomacy and ASEAN charter in examining the efforts that Timor Leste has done in achieving full membership status in this regional organization. The data for the research was collected through secondary sources. The study concluded that Timor Leste has boosted its bargaining position in the last few years and its acceptance into ASEAN is only a matter of time.